2016
DOI: 10.1016/j.actbio.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative effects of peptide nanofibers in an experimental model of Parkinson’s disease

Abstract: Biomimetic nanomaterials bearing natural bioactive signals which are derived from extracellular matrix components like laminin and heparan sulfates provide promising therapeutic strategies for regeneration of the nervous system. However, no research has been reported exploring the use of biomimetic materials against degeneration in Parkinson's disease. In this work, we investigated potential therapeutic effects of heparan sulfate and laminin mimetic PA nanofibers on reduction of striatal injury in experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…This indicates that HOTAIRM1 upregulation may be responsible for the inflammatory cytokine expression in leukocytes (Supplementary Figure 3). We also examined the expression of the four lncRNAs in SH-SY5Y cells stimulated with 6-OHDA, an in vitro system often used in PD study (Sever et al, 2016). Consistent with our findings in PD patients, AC131056.3-001, HOTAIRM1, and RF01976.1-201 expression were significantly increased in SH-SY5Y cells after 6-OHDA stimulation (Figure 7D).…”
Section: Upregulation Of Lncrnas In Human Monocytic and Neuroblastomasupporting
confidence: 83%
“…This indicates that HOTAIRM1 upregulation may be responsible for the inflammatory cytokine expression in leukocytes (Supplementary Figure 3). We also examined the expression of the four lncRNAs in SH-SY5Y cells stimulated with 6-OHDA, an in vitro system often used in PD study (Sever et al, 2016). Consistent with our findings in PD patients, AC131056.3-001, HOTAIRM1, and RF01976.1-201 expression were significantly increased in SH-SY5Y cells after 6-OHDA stimulation (Figure 7D).…”
Section: Upregulation Of Lncrnas In Human Monocytic and Neuroblastomasupporting
confidence: 83%
“…[52][53][54] Furthermore, it has been reported that carbon nanotubes induced fibrogenesis on nanostructured substrates. 55 Moreover, nanoparticles are 100 times smaller than normal red blood cells, which increase the potential for interaction, and there is evidence that nanoparticles interact with proteins, DNA, 56 lung cells, and viruses. The current assumption is that nanoparticles such as silica featured as hydrophilic, hydrophobic, or even amphiphilic that can be taken up by human membranes may pose serious threats.…”
Section: Introduction Of Nanoparticlesmentioning
confidence: 99%
“…The researchers observed that the scaffold was well tolerated and could maintain the cells alive for an extended period . Peptide amphiphiles scaffolds made from lamin and heparan sulfate possesses the quality of being ECM mimetic have also showed potential as PD treatment moderators …”
Section: Tissue Engineering Scaffolds For Alzheimer’s and Parkinson'smentioning
confidence: 99%